Quantization Effects on DeepSeek-1.3B Throughput and GSM8K-V Accuracy - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What is the impact of quantization techniques (e.g., 4-bit vs 8-bit) on DeepSeek-1.3B's inference throughput and accuracy in solving GSM8K-V math word problems. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.2/10. This report is a machine-generated literature synth
Machine-generated literature synthesis.